Fondaparinux in a critically Ill patient with heparin-induced thrombocytopenia: A case report. Issue 37 (September 2018) - He, Yumiao; He, Huaiwu; Liu, Dawei; Long, Yun; Su, Longxiang; Cheng, Wei
Abstract: Rationale: Fondaparinux, as a factor Xa-inhibitor, is used off label to manage heparin-induced thrombocytopenia (HIT), but little experience with HIT patients has been reported in the literature. Moreover, the use of fondaparinux for full anticoagulation in critically ill patients with HIT and renal insufficiency is limited. Patient concerns: A trauma patient, who had received low molecular weight heparin (LMWH) and heparin to treat venous thromboembolism, developed thrombocytopenia and multiple organ dysfunction in the intensive care unit (ICU). Also, her deep venous thromboembolism (DVT) continued to progress. Diagnosis: The final diagnosis was HIT. Interventions: Fondaparinux was temporarily used for anticoagulation treatment of DVT for 7 days when another anticoagulant (argatroban) was unavailable. Although the patient had kidney dysfunction, a full therapeutic dose of 7.5 mg fondaparinux was administered every morning through subcutaneous injection for consecutive 7 days. Outcomes: The patient's thrombocytopenia and thrombosis were successfully treated without bleeding complications during therapeutic fondaparinux administration. Lessons: This is the first case reporting the successful use of fondaparinux for full anticoagulation for DVT in a critically ill patient with HIT and renal insufficiency. Our experience suggests that fondaparinux might be an alternative for anticoagulation treatment in patients with HIT and kidney dysfunction if another anticoagulant (argatroban) is unavailable.